Sentinel Lymph Node Biopsy in Cutaneous Squamous Cell Carcinoma Series of 37 Cases and Systematic Review of the Literature - Raphael Lhote; Jérôme Lambert; Julie Lejeune; Jeremy Gottlieb; Antoine Badaoui; Maxime Battistella; Jennifer Roux; Cecile Pages; Laetitia Vercellino; Catherine Vilmer; Christine Le Maignan; Catherine Escande; et al. (Medical Journals Sweden, 2018)
Cutaneous squamous cell carcinoma (cSSC) is one of the most common skin cancers and can lead to patient death. Early detection of node metastasis is a major goal for dermatologists and oncologists. The procedure sentinel lymph node biopsy has been proposed to improve early detection of node metastasis. The aim of this study was to evaluate the efficacy and impact of this technique on the prognosis of cSSC. A total of 37 patients (Saint Louis Hospital, Paris, France) who had undergone sentinel lymph node biopsy and 290 cases from the literature were analysed. The mean rate of positive sentinel lymph node biopsy was 0.14 [95% CI 0.09-0.22]. However, relapse-free survival and overall survival were not affected by sentinel lymph node status (log-rank test; p = 0.08 and p = 0.31, respectively), suggesting that this procedure is not mandatory in the management of cSSC.